Privatization of early childhood care and education in Nigeria: it’s gains and pains (2013)
Privatization of education and especially the early childhood education has been perceived as the breakdown of the social ethos of education, cost cutting, making profits from children and negligence on the part of the government. The fact is that the running of private early childhood education in an effective way depends on a number of factors which call for collaborative efforts of both government and other stakeholders to make this level of education achieve its goals as in developed countries of the world. In this paper, the writers look at the perception of Nigeria people towards privatization, the status of early childhood care and education privatization in Nigeria, its gains and pains as well as the way forward.